Ferroptosis in pulmonary fibrosis: pathogenesis and traditional Chinese medicine-driven therapeutic approaches - Xudong Fan; Jiangxin Xu; Jinlong Gao; Jie Zhang; Yu Wang; Yanni Shan; Jingming Luo; Weidong Fei; Xinjun Cai (Frontiers in Cell and Developmental Biology)
Pulmonary fibrosis (PF) is a progressive interstitial lung disease marked by the excessive buildup of fibrous connective tissue, leading to permanent damage to respiratory function due to irreversible changes in lung structure. Despite significant progress in understanding its underlying mechanisms, translating this knowledge into effective prevention or treatment remains a major clinical challenge. Ferroptosis, a form of controlled cellular demise triggered by iron, involves the accumulation of lipid peroxides, resulting in irreversible membrane disintegration and oxidative metabolic failure. Emerging studies suggest that ferroptosis exacerbates PF progression by promoting macrophage polarization, fibroblast proliferation, and extracellular matrix deposition, ultimately leading to alveolar epithelial cell death and fibrotic tissue remodeling. Consequently, targeting ferroptosis presents a promising therapeutic approach, with traditional Chinese medicine (TCM) showing particular potential through its multi-dimensional and holistic mechanisms. TCM compounds, extracts, and bioactive monomers exhibit anti-inflammatory, antioxidant, and multi-target properties that demonstrate significant value in managing PF. To develop innovative therapeutic strategies for PF, this review synthesizes recent progress in elucidating ferroptosis pathways implicated in the pathogenesis of PF and underscores the therapeutic potential of TCM in PF management via ferroptosis inhibition. Moreover, this paper highlights the advantages of integrating nanotechnology with TCM for regulating ferroptosis in PF treatment. In general, this paper will provide new perspectives for advancing research and clinical applications of TCM in the treatment of PF.